Kernel Water Relations and Kernel Filling Traits in Maize (Zea mays L.) Are Influenced by Water-Deficit Condition in a Tropical Environment - Alam, Md. Robiul; Nakasathien, Sutkhet; Molla, Md. Samim Hossain; Islam, Md. Ariful; Maniruzzaman, Md.; Ali, Md. Akkas; Sarobol, Ed; Vichukit, Vichan; Hassan, Mohamed M.; Dessoky, Eldessoky S.; Abd El-Ghany, Enas M.; Brestic, Marian; et al. (Frontiers in Plant Science, 2021)
Two field experiments were executed to evaluate the kernel water relations and kernel filling traits of field-grown maize (var. ‘Pioneer 30B80’, ‘NK 40’ and ‘Suwan 4452’) in a tropical environment. Water deficit was imposed at V10 to V13, V13 to V17, V17 stages. Water deficit imposed at V17 to blister and blister to physiological maturity (PM) stage shortened kernel filling duration by 7 and 11 days, whereas water deficit at anthesis to milk and milk to PM stage shortened kernel filling duration by 5 and 7 days, by advancing physiological maturity and eventual increasing kernel dry weight over kernel water content ratio as compared to control. Field capacity (control) attained higher maximum kernel water content, kernel filling duration, final kernel weight, kernel weight ear-1 whereas water deficit at blister to physiological maturity and milk to physiological maturity resulted in higher kernel water loss rate, kernel filling rate and stem weight depletion (% of kernel weight ear-1). Water deficit at reproductive stages increased kernel filling rate in expt. 1 but it was non-significant in Expt. 2. The hybrid ‘NK 40’ exhibited higher kernel water content, kernel water loss, kernel filling rate and stem weight depletion, indicating a higher contribution of stem reserve for kernel filling due to water deficit induced at relatively later reproductive stages as compared to other hybrids across the water regimes in both experiments. The maximum kernel water content (R2 = 0.85, R2 = 0.41) and kernel filling rate (R2 = 0.62, R2 = 0.37) were positively related with final kernel weight whereas kernel water loss rate (R2 = 0.71, R2 = 0.61) showed negative relationship with days from maximum kernel water content to physiological maturity. In Expt. 2, ‘NK 40’ sustained lower canopy temperature and relatively higher cell membrane stability across water regimes and hybrids. Cellular adaptation of ‘NK 40’ under water deficit from milk to physiological maturity by increasing the number of xylem vessel and simultaneously reducing vessel diameter in leaf mid-rib and attached leaf blade relative to control improved efficient transport of water from root to the shoot under water deficit conditions.